Development of Android Application for Banana Leaf Disease Detection - Chong, Mun Zheng; Md Taujuddin, Nik Shahidah Afifi; Sari, Suhaila (Evolution in Electrical and Electronic Engineering, 2024)
Banana is one of the important commercial fruits and one of the favourite fruits in the world because of its high nutrition content and low cost. However, banana production has declined sharply in the last few years, with about 50% yield loss due to late disease detection. In order to help the farmers detect diseases, an android application for banana leaf disease detection is proposed. This application is not intended to replace the farmer but to assist the farmer in detecting the banana leaf disease efficiently. The method used in this project is the CNN MobileNet algorithm as the core to detect the disease and Android Studio as a platform to develop an application based on the algorithm. In image processing, there are a few steps: image pre-processing, feature extraction, and classification. This proposed system is believed to classify the banana leaf disease efficiently, thus helping the farmers in detecting banana leaf disease once completed.